Is miniscrew primary stability influenced by bone density? - Mariana Marquezan; Margareth Maria Gomes de Souza; Mônica Tirre de Souza Araújo; Lincoln Issamu Nojima; Matilde da Cunha Gonçalves Nojima (Sociedade Brasileira de Pesquisa Odontológica, 2011)
Primary stability is absence of mobility in the bone bed after mini-implant placement and depends on bone quality among other factors. Bone quality is a subjective term frequently considered as bone density. The aim of this preliminary study was to evaluate bone density in two bovine pelvic regions and verify the primary stability of miniscrews inserted into them. Forty bone blocks were extracted from bovine pelvic bones, 20 from iliac and 20 from pubic bone, all of them containing cortical bone about 1 mm thick. Half of the sections extracted from each bone were designated for histological evaluation of bone density (trabecular bone area - TBA) and the other half for bone mineral density (BMD) evaluation by means of central dual-energy X-ray absorptiometry (DEXA). Then, twenty self-drilling miniscrews (INPÒ, São Paulo, Brazil) 1.4 mm in diameter and 6 mm long were inserted into the bone blocks used for BMD evaluation. Peak implant insertion torque (IT) and pull-out strength (PS) were used for primary stability evaluation. It was found that iliac and pubic bones present different bone densities, iliac bone being less dense considering BMD and TBA values (P > 0.05). However, the miniscrew primary stability was not different when varying the bone type (P < 0.05). IT and PS were not influenced by these differences in bone density when cortical thickness was about 1 mm thick.